1985
DOI: 10.1111/j.1365-3032.1985.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of dandelion pollen by adult worker honeybees

Abstract: ABSTRACT. The digestion of dandelion (Taraxacum officinale) pollen by adult worker honeybees (Apis mellifera Linn.; Hymenoptera: Apidae) was initiated at the germination pores. 30 min after feeding, pollen had reached the anterior midgut and the germination pores had become swollen. This permitted further removal of protoplasm during the next 2 h of digestion as the pollen passed into the middle portion of the midgut. 3 h after feeding, pollen grains had reached the posterior midgut where some had ruptured to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 15 publications
1
27
0
4
Order By: Relevance
“…A previous study found that feeding a pollen-free diet for 24 hours results in digestion of previously consumed pollen. 56 In agreement, we have found that bees fed a pollen-free diet for 24 hours have negligible numbers of intact pollen grains in their midgut contents (data not shown) and very low levels of pollen-derived miRNA (Fig. S2A).…”
Section: Negligible Transfer Of Diet-derived Mirna To Internal Tissuesupporting
confidence: 84%
“…A previous study found that feeding a pollen-free diet for 24 hours results in digestion of previously consumed pollen. 56 In agreement, we have found that bees fed a pollen-free diet for 24 hours have negligible numbers of intact pollen grains in their midgut contents (data not shown) and very low levels of pollen-derived miRNA (Fig. S2A).…”
Section: Negligible Transfer Of Diet-derived Mirna To Internal Tissuesupporting
confidence: 84%
“…The extent of pollen digestion is also an important factor in comparing the nutritional value of different pollens to bees (Peng et al, 1985;. For honeybee workers collected from sunflower fields, we have previously recorded an extraction efficiency, adjusted for the empty grains in fresh pollen, of 69% (Human et al 2007).…”
Section: Genotypic Differences Have Been Recorded In Nectar Productiomentioning
confidence: 99%
“…To what extent these processes involve pollen-specific enzymes is not known. Interestingly, an important proportion of the pollen grains of Taraxacum were found to be still intact in the feces of adult honey bee workers (Peng et al 1985), leading to the conclusion that Taraxacum pollen grains could not be completely emptied by the honey bee. The failure of C. rapunculi, C. florisomne, and H. adunca to develop on Asteraceae pollen might be related to similar difficulties in extracting nutrients from the pollen protoplasm.…”
Section: Extraction Of Pollen Nutrientsmentioning
confidence: 99%